PENERAPAN METODE PEMBELAJARAN STUDENT FACILITATOR AND EXPLAINING BERBASIS PETA KONSEP UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA - Masjudin Masjudin; Ni Ketut Resna Arini (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2014)
Students' learning activity and achievement are very low. This is because the teaching method used by the teacher is always monotonous and boring. Therefore, the purpose of this study is to describe the steps of learning methods Student Facilitator and Explaining-based Concept Map in order to improve the activity and learning outcomes of students of grade VII B SMPN 1 Jonggat on the subject matter of square. This research is a classroom action research consisting of two cycles containing planning, implementation, observation and reflection phase. Subjects of this study amounted to 28 students. The research instrument used is the learning achievement test given at the end of each cycle, the observation guideline to get a direct description of the learning activities through the application of learning methods of student facilitator and explaining based on concept maps, as well as interview guidelines to strengthen the research results obtained. The data obtained were analyzed using learning mastery. Indicators of this study is an increase in the average score of student learning outcomes and student learning activities. The results showed an increase in the average score of student learning outcomes in the first cycle of 79.29 with classical completeness 85.71% increased in cycle II to 88.08 with 92.86 classical completeness. The average score of student learning activity in cycle I was 16.48 (active category) increased in cycle II to 18,11 (active category). We conclude that by applying the steps of student learning methods facilitator and explaining based on concept maps in teaching and learning process can improve student activity and learning outcomes